Contextualization of Polygamy Hadith from the Perspective of Double Movement Theory of Fazlur Rahman: A Normative and Historical Examination of Gender Justice Practices in Islam - Sulhayani, Sulhayani; Halim, Abdul (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
Hadiths about polygamy are often debated in contemporary religious discourse, especially in relation to gender justice and women's rights. Although polygamy is permitted in Islam through the Qur'an and hadith, a literal understanding of these texts often leads to practices that do not reflect justice as the core of Islamic teachings. This study aims to examine hadiths on polygamy using a contextual approach through Fazlur Rahman's double movement theory. This study uses a qualitative method with a library research approach, where the main sources examined are hadith books, classical and contemporary tafsir, and the works of Fazlur Rahman. The double movement theory offers two steps of analysis: first, understanding the historical-sociological context of the hadith during the time of the Prophet; second, extracting universal moral values that are relevant for application in the present context. The findings indicate that polygamy in hadith does not aim to normalize patriarchal relationships but rather serves as a response to specific social situations, such as protecting widows and orphans. Implications suggest the need for a more ethical, historical, and socially responsive interpretative approach to ensure that the understanding of hadith remains aligned with the principles of justice and gender equality in Islam.